Integrated pest management strategies for controlling Etiella zinckenella in peanut cultivation: field evaluation of sustainable approaches - Prayogo, Yusmani; Ginting, Sempurna; Bayu, Marida Santi Yudha Ika; Indiati, Sri Wahyuni; Baliadi, Yuliantoro; Harnowo, Didik (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2025)
Etiella zinckenella is a significant pest of peanuts in Indonesia, causing pod yield losses of up to 100% in infested fields. This study aims to identify an appropriate strategy for the sustainable management of E. zinckenella by validating the effectiveness of various integrated pest management approaches through field trials. The experiment was conducted in two locations, Natar (Lampung) and Muneng (East Java), using 11 treatment combinations with three replications. The peanut variety planted was Gajah (GH 51). The treatments included a range of pest control technologies, such as seed treatment with thiamethoxam, application of carbofuran, neem seed powder (NSP), release of Trichogrammatoidea bactrae-bactrae, application of Spodoptera litura Nuclear Polyhedrosis Virus (SlNPV), trap crops (Crotalaria, soybean, maize, mung bean), organic fertilizer, and lambda-cyhalothrin. The findings revealed that the population density of pod borers and the extent of pod and seed damage were higher in Natar than in Muneng. In Natar, pod damage ranged from 43.7% to 76.3%, with the highest levels recorded in untreated plots and those treated with lambda-cyhalothrin. Similarly, the highest pest population densities in Natar were observed in untreated plots and those treated with lambda-cyhalothrin. In contrast, Muneng exhibited significantly lower pod damage, ranging from 0.2% to 2.6%, with the highest recorded damage at 2.64%. The most effective pest management strategy in both locations was a combination of thiamethoxam seed treatment, carbofuran, NSP, T. bactrae-bactrae, SlNPV, and Crotalaria trap crops, which reduced pod damage to 43.7% in Natar and 0.2% in Muneng. These results suggest that an integrated pest management approach effectively mitigates E. zinckenella infestations in endemic areas. This method not only minimizes pest damage but also helps maintain populations of natural enemies, including Formicidae, Coccinella sp., Paederus sp., and Oxyopes sp., thereby supporting ecological balance. Furthermore, trap crops such as maize, soybean, and mung bean, when planted around peanut fields, demonstrated considerable efficacy in reducing pest attacks compared relative to chemical insecticides, highlighting their potential for a sustainable pest management strategy.